Geotourism Role As One Of Sustainable Developement Factors - Ibrahim M. Abou El Leil, Ali M. Al Faitory , Abdelsalam Saleh (Journal of Pure & Applied Sciences, 2020)
This study has been conducted on the eastern region which parallel to the coastal strip in the northeastern of Libyan coast encountered between Bomba bay in the west, Mousaed in the east, Jaghboub in the south and the Mediterranean Sea in the north, between Longitudes 23̊ 10'' 00' and 25̊ 15'' 00' and Latitudes 31̊ 50'' 00' and 32̊ 45'' 10'. The objective of this study is the assessment of geotourism potentialities of some locations such as Ain Al Ghazalah, Wadi Al Sal (Tobruk), Wadi Abou Al Gomel (Tobruk), Wadi Al Raheb (Kambout), Wadi Rezq (Al Bordy), Wadi Al Sawani (Al Bordy) and Al Jaghboub Oasis. These geosites denoted by GS1, GS2, GS3, Gs4, GS5, GS6 and GS7 respectively. In this study the matrix models for geotourism potentialities analysis have been applied for the different geosites according to a certain factors and values that varies from location to another by using the geosites assessment model (GAM) with values index range between 0.0 and 1.0. Also SWOT (strength, weakness, opportunity, threats) and TOWS analyses have been applied to evaluate these geosites to achieve sustainable development. The GAM model of matrix consists of two groups, main values (MV) and additional values (AV) that representing an indicators of assessment. The results obtained from models analysis revealed that there is a variation of potentialities between the studied geosites according to indicators and subindicators. Throughout the GAM matrix analysis based on main and additional values, the seven geosites are represented in three zones of matrix, whereas, GS2,GS4 and GS5 in zone Z11, while GS1 in zone Z21. The other geosites GS3, GS6 and GS7 are represented in a good locations in the matrix, and this is attributed to their higher values of MA and AV. On other hand, the three geosites GS2, GS4 and GS5 have a lower MA and AV values, so they are represented in zone Z11.